2013
DOI: 10.1590/s1984-82502013000200015
|View full text |Cite
|
Sign up to set email alerts
|

Rational use of medicines: prescribing indicators at different levels of health care

Abstract: This multicenter study aimed to investigate prescribing patterns of drugs at different levels of health care delivery in university-affiliated outpatient clinics located in eight cities in the South and Midwest of Brazil. All prescriptions collected were analyzed for various items, including WHO prescribing indicators. A total of 2,411 prescriptions were analyzed, and 469 drugs were identified. The number of drugs prescribed per encounter, the frequency of polypharmacy, and the percentage of encounters with at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 20 publications
0
20
1
3
Order By: Relevance
“…In 2016, the percentage of generic prescription in USA was 84.6 percent 22 . One multicentre study in eight cities of South and Midwest of Brazil reported that most drugs (86.1%) were prescribed by generic name 28 . In The Bangladesh, court ordered that 'doctors must use generic drug names rather than specifying particular brands.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, the percentage of generic prescription in USA was 84.6 percent 22 . One multicentre study in eight cities of South and Midwest of Brazil reported that most drugs (86.1%) were prescribed by generic name 28 . In The Bangladesh, court ordered that 'doctors must use generic drug names rather than specifying particular brands.…”
Section: Resultsmentioning
confidence: 99%
“…The Government of Bangladesh controls the price of 209 generic drugs in specified dosage forms, along with 41 active pharmaceutical ingredients produced in the country and medicine imports [26][27] .Nonetheless, irrespective of the level of healthcare delivery system, prescribing drugs by generic name reduces duplicity, improves access to medicines, and subsequently, escalates patient compliance with drug therapy and disease control. It is expected that emphasizing to medical students about generic medicines will improve and promote rational prescribing 28 . Lack of official channels to announce the patent status of major drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the FDC available in Indian market lack therapeutic rationale for their use, leading to wasteful expenditure. [11][12][13] Most commonly prescribed FDC was pantoprazole domperidone followed by muscle relaxant NSAID combination, and others. Most of the FDCs (62%) were rational as per WHO Essential Medicine List.…”
Section: Discussionmentioning
confidence: 99%
“…11,13,14 Similar studies in Pakistan (83.1%), Nepal (84%), Northern Ethiopia (93.3%), Brazil (86.1%), China (96.12%) noted better results. [15][16][17][18][19] The WHO endorses prescribing medication by its generic name. It enables easy identification of medication and better communication between health care providers.…”
Section: Discussionmentioning
confidence: 99%